Reformulation Of Value Added Tax (Vat) Tariff Policy In Indonesia - Sipayung, Bonarsius (Journal of Tax Law and Policy, 2023)
The dominance of certain groups of people who criticise the increase in the Value Added Tax(VAT)rate in Indonesia to 12% since 1 January 2025 and the scarcity of studies or research related to the review of the VAT rate increase in Indonesia, it is necessary to conduct a juridical and philosophical review of the VAT rate increase policy. Based on a normative juridical study, two conclusions are drawn in this study. First, the VAT rate regulation in Indonesia has been regulated since the enactment of the VAT Law in 1983. Second, an increase in VAT rates above 11% can be achieved by reformulating the VAT rate policy in handling the challenges of digitalisation while still considering the principles of justice and appropriate targeting. It is recommended that the VAT rate increase consider other VAT policy improvements, such as removing the imposition ofVAT on necessities, health services, education services, social services, and other services, imposing special rates on certain types of goods/services, namely Final VAT, and adjusting the VAT threshold.